SHARIA ECONOMIC LAW ON THE GROWTH OF MICRO, SMALL, AND MEDIUM ENTERPRISES (UMKM) IN THE DIGITAL ERA - Safitri, Meisa Nur; Nurkhafiah, Nabila; Nurzihan, Siti; Turromaniyah, Afifa (JURNAL HAKAM, 2025)
The growth of MSMEs in the digital era requires strong Sharia governance, the expansion of Sharia-based fintech, and the enhancement of Islamic economic literacy to ensure that digital transformation proceeds fairly and sustainably. This study examines the relevance of Sharia Economic Law in promoting the growth of MSMEs amid rapid digital transformation. In an era where online transactions, digital payments, and fintech platforms dominate the business ecosystem, Islamic legal principles such as justice (‘adl), transparency (shafafiyyah), and the prohibition of riba and gharar are increasingly important to implement. Using a qualitative descriptive approach, this research analyzes how Sharia-based financial regulations and innovations influence MSME development. The results show that digital Sharia financing provides broader and more ethical access to funding for MSMEs. However, challenges remain, including low digital literacy, weak supervision of Sharia compliance, and a lack of regulatory synergy between national economic policies and Islamic economic principles.